DETERMINANTS OF INNOVATION: AN EVIDENCE-BASED PERSPECTIVE IN THE DIGITAL TRANSFORMATION ERA - Akhmadi, Saltanat (School of Engineering and Digital Sciences, 2023)
Innovation, the process of finding and using new ideas, creating new products or services, and introducing them to the market, is widely celebrated as the driving force of economic growth, sustainable development, and social change. Yet, innovation activity around the world is mostly concentrated in a few leading countries that possess the human and financial capital to create new knowledge and the market acumen to capitalize on it. For instance, three quarters of the patent filings from global innovation hotspots are emerging from just four countries – USA, Japan, China, and Germany. This uneven concentration of inventive activity, aptly named the global innovation divide, increases the gap between developed and developing economies. The situation has exacerbated over the last decade with the fourth industrial revolution and the emergence of the digital economy that has brought to the forefront knowledge generation and utilization. To close the innovation gap, regional, national, and international governments and authorities constantly encourage innovation through an array of fiscal subsidies and regulatory interventions with admittedly mixed results. Innovation of course starts at the firm level, with innovative firms developing competitive advantages for themselves and for their regions through knowledge exploration and exploitation and the creation of new technologies. Even in innovation leaders such as Germany, roughly one in two enterprises do not engage in innovation. Obstacles to innovation reflect the realization that innovation is a difficult, financially risky, and mostly liable to fail process. A multitude of business surveys and research studies have been dedicated to identifying and assessing the importance of the obstacles that deter firms from innovating and contrasting them with the obstacles slowing down, but not stopping, firms already engaged in innovation. While there is a broad consensus on what constitutes an obstacle to innovation, the term is open to a wide range of interpretations that are largely contingent upon the context within which innovation occurs. This handicaps the effectiveness of innovation policies that are based upon a generic understanding of the innovation process and are not sufficiently nuanced for the digital era. Past research on innovation has sought to identify major correlates of innovation by assessing only one dimension of innovative behavior at each time. Treating the phenomenon of innovation as unidimensional does not sufficiently capture the richness of the construct of organizational innovation. This dissertation demonstrates instead that the process of innovation is decidedly multi-dimensional and explores the multi-faceted nature of the impact of innovation on firms, regions, and countries. Based on an extensive range of publicly available datasets and using a multi-dimensional analytical approach, this dissertation dissects the phenomenon of innovation at several layers of abstraction: the firm layer, the operational layer, the process layer and the policy layer. The contributions of this dissertation at each layer are addressed in turn. • At the firm layer, the key characteristics of the profile of an organization that impact its involvement in innovation activities are identified as firm size, sector, and prior engagement in innovation activities. • At the operational layer, the effect of factors present in the operational environment within which innovation occurs is measured with emphasis on economic, market, cultural and gender diversity issues. • At the process layer, issues related to knowledge acquisition, elicitation, and management in innovative firms are introduced and examined in the context of tangible innovation outputs such as intellectual property rights. • At the policy layer, the effect of innovation policies and interventions over the last decade is assessed with a special focus on the promotion of clustering activities and innovation hotspots. The results of this evidence-based dissertation presented herein are instrumental in defining the specific facets of an effective, modern innovation policy, producing the desired performance outcomes in a context of limited resources for innovation.
Keywords: type of access: open access; Digital Transformation